(untitled) (Ukrainian Journal of Ophthalmology, 2024)
The incidence of blindness due to exudative retinal diseases reduced significantly over the twenty years of the use of anti-vascular endothelial growth factor (VEGF) therapy in ophthalmology. However, despite advances in recent years, current outcomes of anti-VEGF therapy for exudative retinal diseases are not always optimal. This review aims to highlight the advances in the development of VEGF inhibitors and identify potential ways of improving the outcomes of anti-VEGF therapy for, and solving current problems in the management of, exudative retinal diseases.